Comparison of Compliance and Intervention Outcomes Between Hip- and Wrist-Worn Accelerometers During a Randomised Crossover Trial of an Active Video Game Intervention in Children. - Howie, Erin; McVeigh, Joanne; Straker, Leon (Human Kinetics, Inc, 2016)
Background: There are several practical issues when considering the use of hip-worn or wrist-worn accelerometers. This study compared compliance and outcomes between hip- and wrist-worn accelerometers worn simultaneously by children during an active video games intervention. Methods: As part of a larger randomized crossover trial, participants (n=73, age 10-12 years) wore 2 Actical accelerometers simultaneously during waking hours for 7 days, on the hip and wrist. Measurements were repeated at 4 timepoints: 1) at baseline, 2) during traditional video games condition 3) during active video games condition 4) during no video games condition. Compliance and intervention effects were compared between hip and wrist. Results: There were no statistically significant differences at any timepoint in percentage compliance between hip (77-87%) and wrist (79-89%). Wrist-measured counts (difference of 64.3 counts per minute, 95% CI 4.4, 124.3) and moderate-to-vigorous physical activity (MVPA) (12 min/day, 95% CI 0.3, 23.7) were higher during the no video games condition compared to the traditional video games condition. There were no differences in hip-measured counts per minute or MVPA between conditions or sedentary time for hip or wrist. Conclusions: There were no differences in compliance between hip- and wrist-worn accelerometers during an intervention trial, however, intervention findings differed between hip and wrist.